Sabedoria Adinkra: vivências e ressignificações artísticas a partir de símbolos africanos - Seragi, Mariana Santana [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present work is guided by the proverbial meanings of three Adinkras symbols, components of West African Akan writing. These symbols that direct the development of this research. First Sankofa presents itself as an emblem, guiding the reconnection with ancestral narratives and understanding of the perspectives of distinct realities in the black mother and white father family configuration. The movement of recognition of these origins unfolds in Epa, as a driver for the thought of the change of eugenicist paradigms present in the work A Redenção de Cam by Modesto Brocos, thus performing the artistic transcoding of this image with the collaboration of three contemporary visual artists who brought new interpretations and meanings sensitive to the painting of 1885. Totaling this experience with Adinkrahene, a symbol that propagates the learning experienced in this process, transformations are enhanced that can resignify the black stories that were prevented from being told. The entire composition of this work is in union with the production of an Artist's Book that brings together all the plastic developments of this research.

O presente trabalho guia-se a partir das significações proverbiais de três símbolos Adinkras, componentes da escrita Akan da África Ocidental. Símbolos estes que direcionam o desenvolvimento desta pesquisa. Primeiramente Sankofa se apresenta como emblema, orientando a reconexão com narrativas ancestrais e entendimento das perspectivas de realidades distintas na configuração familiar materna negra e paterna branca. O movimento de reconhecimento destas origens desenrola-se em Epa, enquanto impulsionador para o pensamento da mudança de paradigmas eugenistas presentes na obra A Redenção de Cam de Modesto Brocos, executando assim, a transcodificação artística desta imagem com a colaboração de três artistas visuais contemporâneas que trouxeram novas interpretações e significados sensíveis a pintura de 1885. Totalizando esta experiência com Adinkrahene, símbolo que propaga os aprendizados vivenciados neste processo, potencializa-se transformações que possam ressignificar as histórias negras que foram impedidas de serem contadas. Toda a composição do presente trabalho está em união com a produção de um Livro de Artista que reúne todos os desdobramentos plásticos desta investigação.
Adinkra wisdom: experiences and artistic resignifications from African symbols
Keywords: Interracial ancestry; Artistic transcoding; Artist's book; Artistic resignifications; Life story; Adinkras; Ancestralidade inter-racial; Transcodificação artística; Livro de artista; História de vida